2014
DOI: 10.11607/jomi.3379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Connective Tissue Grafting on the Facial Gingival Level Following Single Immediate Implant Placement and Provisionalization in the Esthetic Zone: A 1-Year Randomized Controlled Prospective Study

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
233
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(251 citation statements)
references
References 0 publications
10
233
3
5
Order By: Relevance
“…Superior aesthetic outcomes can be expected (i.e., papilla height and level of the marginal mucosa) when soft tissue grafting is performed concomitantly with immediate implant placement, as well as there is a lack of data for soft tissue substitutes [ 19 ]. Overall, Yoshino et al [ 20 ] reported that immediate implant placement and provisionalization with an SCTG presented less change of the level of the buccal peri-implant mucosa when compared to sites that did not undergo an SCTG.…”
Section: Critical Summary Of the Results Of Systematic Reviewsmentioning
confidence: 99%
“…Superior aesthetic outcomes can be expected (i.e., papilla height and level of the marginal mucosa) when soft tissue grafting is performed concomitantly with immediate implant placement, as well as there is a lack of data for soft tissue substitutes [ 19 ]. Overall, Yoshino et al [ 20 ] reported that immediate implant placement and provisionalization with an SCTG presented less change of the level of the buccal peri-implant mucosa when compared to sites that did not undergo an SCTG.…”
Section: Critical Summary Of the Results Of Systematic Reviewsmentioning
confidence: 99%
“…30 When SCTG is used with immediate implant placement and provisionalization in the esthetic zone it significantly improves maintenance of facial gingival level. 31 Grunder 32 measured the dimension of the labial volume before and 6 months after implant placement in the maxillary anterior area with or without SCTG using a flapless tunnel technique. The nongrafted group had an average 1.063-mm loss of volume, whereas the grafted group presented with a slight gain of 0.34 mm.…”
Section: Soft Tissue Management At the Time Of Implant Placementmentioning
confidence: 99%
“…Pour améliorer l'esthétique, renforcer le biotype et péren-niser la stabilité des tissus péri-implantaires, un greffon de tissu conjonctif est prélevé, enfoui puis stabilisé au niveau vestibulaire [14] (Fig. 11 et 12).…”
Section: Fig 6 Temporary Prosthesis (Artech Laboratory)unclassified